2004
DOI: 10.1191/0959683604hl715rp
|View full text |Cite
|
Sign up to set email alerts
|

Past uppermost tree limit in the Central European Alps (Switzerland) based on soil and soil charcoal

Abstract: The uppermost limits of past treelines in the Alps are established using soil type and soil charcoal mass. In all the studied sites, a sharp decrease of soil charcoal mass is correlated with the upper altitudinal limit of podzols. On the basis of this evidence, the uppermost tree limit reached 2500i: 100m a.s.l. in the Valaisan Alps during the Holocene, i.e., it was 250 100m higher than today's potential treeline. Consequently, the timberline would have reached 2400 100m a.s.l.. From the strong decline of char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 36 publications
3
28
2
2
Order By: Relevance
“…Pedoanthracological studies based on plant identification of soil charcoal in the internal zones of the Alps show that subalpine grasslands result from deforestation over time-scales of centuries to millennia Talon et al, 1998;Carnelli et al, 2004), including fires that have become more frequent since at least ca. 6000 years BP (Carcaillet, 1998;David and Barbero, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pedoanthracological studies based on plant identification of soil charcoal in the internal zones of the Alps show that subalpine grasslands result from deforestation over time-scales of centuries to millennia Talon et al, 1998;Carnelli et al, 2004), including fires that have become more frequent since at least ca. 6000 years BP (Carcaillet, 1998;David and Barbero, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies report the masses of soil charcoal and if they do, the masses are often derived from different profile depths. For example, Carnelli et al (2004) found much less charcoal (up to 19.35 mg kg −1 ) in an alpine Podzol (10-30 cm depth), or an average of 6.18 mg kg −1 in soils below 2400 m a.s.l. Carcaillet and Talon (2001) reported charcoal masses of 102-863 mg kg −1 (800-1280 kg ha −1 ) in soils under temperate Fagus-Abies forests.…”
Section: Incorporation Of Charcoal From the Forest Floor Into The Soimentioning
confidence: 99%
“…evidenced a downward shifting of the treeline by about 150 m from the early Holocene to the present. Several studies carried out in the French Alps (eg, David, 1993), in Scotland (Pears, 1968) and in Switzerland (Carnelli et al, 2004a), have demonstrated that during the Preboreal and Boreal period (c. 9500-7000 cal. BP; Maisch et al, 1999) the treeline was about 200-250 ± 100 m higher than today.…”
Section: Fire Regimes and Human Impactmentioning
confidence: 99%
“…Furthermore, soil charcoal dating gives a time proxy for soil pedogenesis (Carcaillet, 2001) and can be used to estimate soil age. Charcoal fragments have been widely used especially in studies about treeline shifting, soil pedogenesis, fire regimes, changes in vegetation and carbon storage (eg, Berli et al, 1994;Cherubini et al, 1995;Carcaillet and Brun 2000;Carcaillet, 2001;Carnelli et al, 2004a;Ali et al, 2005;Hajdas et al, 2007;Bélanger and Pinno, 2008;DeLuca and Aplet, 2008). Charcoal identification and dating is a powerful tool to reconstruct past human impact on Alpine territories.…”
Section: Introductionmentioning
confidence: 99%